2008
DOI: 10.1016/j.micres.2006.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and initial characterization of the tellurite reducing moderately halophilic bacterium, Salinicoccus sp. strain QW6

Abstract: Among the 49 strains of moderately halophilic bacteria isolated from the salty environments of Iran, a Gram-positive coccus designated as strain QW6 showed high capacity in the removal of toxic oxyanions of tellurium in a wide range of culture medium factors including pH (5.5-10.5), temperature (25-45 degrees C), various salts including NaCl, KCl, and Na(2)SO(4) (0.5-4 M), selenooxyanions (2-10 mM), and at different concentrations of potassium tellurite (0.5-1 mM) under aerobic condition. Phenotypic characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
47
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(51 citation statements)
references
References 30 publications
4
47
0
Order By: Relevance
“…Further evidence for this proposal is the observed presence of small black deposits following growth of H. influenzae in the presence of sublethal levels of tellurite (data not shown). These deposits have been reported with other organisms challenged with tellurite and are presumed to be insoluble tellurium (elemental) (Chasteen & Bentley, 2003;Amoozegar et al, 2008). The deposits were observed in cultures of both the wild-type and the tehB deletion mutant strains and indicate that the reduction of tellurite to the insoluble metalloid proceeds in the absence of tehB.…”
Section: Discussionsupporting
confidence: 62%
“…Further evidence for this proposal is the observed presence of small black deposits following growth of H. influenzae in the presence of sublethal levels of tellurite (data not shown). These deposits have been reported with other organisms challenged with tellurite and are presumed to be insoluble tellurium (elemental) (Chasteen & Bentley, 2003;Amoozegar et al, 2008). The deposits were observed in cultures of both the wild-type and the tehB deletion mutant strains and indicate that the reduction of tellurite to the insoluble metalloid proceeds in the absence of tehB.…”
Section: Discussionsupporting
confidence: 62%
“…Bacillus Mk22 secreted protease with maximum activity after 7 days; clear zones (24 mm) indicated high proteolytic activity, which was similar to previously reported data (Amoozegar et al, 2008). Protease production was tested at different parameters, in which the maximum production was attained at 45°C (Figure 3), pH 8 (Figure 4), and 12% NaCl ( Figure 5).…”
Section: Resultssupporting
confidence: 91%
“…Amoozegar et al (2008) found a moderately halophilic Gram-positive coccus designated as Salinicoccus sp. strain QW6 showing high capacity in the removal of toxic oxyanions of tellurium under a wide range of factors.…”
Section: Detoxification Of Heavy Metalsmentioning
confidence: 99%